Optimalizace rozdělení poplatků za služby jako možnost navýšení konkurenceschopnosti komerčních nemovitostí - Khitilova, Ekaterina; Mihola, Marek; Chmela, Ladislav (Univerzita Pardubice, 2013)
The article is focused on the issue of allocation of service charges for commercial (office) properties. The article describes several existing methods of the service charges allocation. Advantages and disadvantages of the methods are described on illustrative examples. The main goal of this article is to analyse the possibilities of increasing competitiveness of commercial property lease companies by optimizing costs of the services charges. This main goal can be divided into sub-goals to prepare this article: 1. Description of characteristics of the commercial property lease business. 2. Description of current status of the service charges allocation between tenants in commercial premises. 3. Assessment of options to increase the competitiveness of the commercial property (office) landlords. 4. Preliminary assessment of the proposed options and their possible advantages and disadvantages, including expected impacts of application of the specific solution compared to the existing practice. Authors formulate opinions on the optimization of the service charges allocation to increase the competitiveness in the commercial property business in the conclusion.
Optimization of the service charges as a possibility to increase competitiveness in commercial property business
Keywords: service charges; commercial property; lease; competitiveness